Influence of Tin Doped Cadmium Oxide on Structural and Optical Properties by Laser Induced Plasma - A.Aadim, Kadhim; S. Jasim, Awatif; M. Hussein, Jasim (International Journal of Psychosocial Rehabilitation, 2020)
In this research, the structural and optical properties of pure cadmium oxide films (CdO) prepared by pulsed laser sedimentation technique (PLD) in the vacuum were studied. Also, the effect of tin inoculations with tin ratios (0.1, 0.3, 0.5) was studied on the structural and optical properties of cadmium oxide films. Crystallization of the prepared membranes through X-ray diffraction technology (XRD), which showed that the synthesis of the prepared membranes is polycrystalline, and AFM images also showed that increased tin vaccination resulted increased the grain size and decreased surface roughness, as well as the absorption coefficient and the optical energy gap. For prepared films, It was found that both the absorption coefficient and the energy gap increase with the increase in the percentage of vaccination .